Respuesta :

Answer:

[tex](x ^ 2 -1)(x ^ 2 -8)\\\\x = 2\sqrt{2}\\\\x = - 2\sqrt{2}\\\\x = 1\\\\x = -1[/tex]

Step-by-step explanation:

We have the following equation [tex]x^4 - 9x2 + 8 = 0[/tex]

To solve this problem, do:

[tex]u = x ^ 2[/tex]

then it has:

[tex]u ^ 2 - 9u + 8 = 0[/tex]

Then he has a second-degree equation.

To resolve factor.

You must find 2 numbers that when you add them get -9 and multiply them get 8.

These numbers are:

u = -1 and u = -8

Then it has:

[tex](u-1)(u-8) = 0[/tex]

[tex]u = 1[/tex]

and

[tex]u = 8[/tex]

Remember that [tex]u = x ^ 2[/tex]

Then it has:

[tex](x ^ 2 -1)(x ^ 2 -8)\\\\x = 2\sqrt{2}\\\\x = - 2\sqrt{2}\\\\x = 1\\\\x = -1[/tex]

ANSWER

[tex]x = \pm 2\sqrt{2} \: or \: {x}= \pm1[/tex]

EXPLANATION

Given;

[tex] {x}^{4} - 9 {x}^{2} +8 = 0[/tex]

We can rewrite as

[tex] ({x}^{2} )^{2} - 9 {x}^{2} +8 = 0[/tex]

Let

[tex]u = {x}^{2} [/tex]

This implies that,

[tex] u^{2} - 9u +8 = 0[/tex]

This implies that,

[tex] u^{2}-u - 8u +8 = 0[/tex]

[tex]u(u - 1) - 8(u - 1) = 0[/tex]

[tex](u - 1)(u - 8) = 0[/tex]

[tex]u = 8 \: or \: u = 1[/tex]

But

[tex]u = {x}^{2} [/tex]

This implies that,

[tex] {x}^{2} = 8 \: or \: {x}^{2} = 1[/tex]

[tex] x = \pm \sqrt{8} \: or \: {x}= \pm \sqrt{1} [/tex]

[tex] x = \pm 2\sqrt{2} \: or \: {x}= \pm1[/tex]